2013
DOI: 10.1111/1475-4932.12075
|View full text |Cite
|
Sign up to set email alerts
|

The Immigrant Wage Gap and Assimilation in Australia: Does Unobserved Heterogeneity Matter?

Abstract: Immigrants to Australia are selected on observable characteristics. They may also differ from natives on unobservable characteristics such as ambition or motivation. If we account for unobservable differences, we find a wage gap for immigrant men from English‐speaking backgrounds, in contrast with previous research which has found no wage gap. Controlling for unobserved heterogeneity also seems important for finding cohort effects. Immigrants that arrived before 1985 faced a larger wage gap compared to native‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 46 publications
(63 reference statements)
0
19
0
Order By: Relevance
“…A wide range of studies have found migrants from language other than English backgrounds have inferior labour market outcomes compared to migrants from English‐speaking backgrounds in Australia (Borooah & Mangan ; Ho & Alcorso ; Breunig et al. ). The significant variation in proficiency in English between different Asian birthplace and ancestry groups may affect their employment outcomes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A wide range of studies have found migrants from language other than English backgrounds have inferior labour market outcomes compared to migrants from English‐speaking backgrounds in Australia (Borooah & Mangan ; Ho & Alcorso ; Breunig et al. ). The significant variation in proficiency in English between different Asian birthplace and ancestry groups may affect their employment outcomes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is argued that such immigrants should enjoy faster rates of labour market assimilation in the host country Miller, 2008, 2009). Australian data provide empirical evidence to support this argument for the case of English-speaking background (ESB) immigrants, who (relative to non-English speaking background (NESB) immigrants) also enjoy greater 'cultural proximity' to Australian labour market institutions (Breunig et al, 2013). There is also evidence of labour market assimilation for NESB immigrants, often attributed to their relatively high levels of human capital (Green et al, 2007).…”
Section: Introductionmentioning
confidence: 93%
“…This approach differs from much of the existing literature, which tends to examine economic assimilation by looking at levels of (un)employment or wages (Antecol et al, 2006;Breunig et al, 2013). Focusing on occupational attainment is useful, in that disadvantage in the labour market is not limited to employment status and earnings; occupational mobility is also important because an individual's occupation may provide a broader signal of their economic and social well-being (Dex et al, 2007;Kostenko et al, 2012;Nickel, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…Building on the seminal work of Chiswick () and Borjas (), many studies focus on improving our understanding of the factors driving the immigrant earnings gap and on assessing the extent to which various immigrant cohorts are able to successfully catch up to their native‐born counterpart over time; see recent contributions by Butcher and DiNardo (), Adsera and Chiswick (), Breunig et al . (), among many others. The literature has also explored other dimensions believed to shape the socioeconomic performance of immigrants such as occupational attainment (Green, ; Frenette et al ., ), employment (Gorinas, ), homeownership (Borjas, ; Sinning, ), and wealth (Bauer et al ., ).…”
Section: Introductionmentioning
confidence: 97%